Iowa Birdline update, November 10, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for November 10, 1993. Highlights include sightings of Evening Grosbeaks, a White-winged Crossbill, Snowy Owls, Scoters and a Pacific Loon. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed